Nasionalisme Tenaga Kerja Indonesia (TKI) Di Malaysia dalam Narasi Media Sosial - Maksum, Ali; Surwandono, Surwandono (Nation State: Journal of International Studies, 2018)
This article discusses the nationalism sentiment among Indonesian migrant workers in Malaysia from the social media narratives. The aims of this article are (1) to examine the framing of nationalism among Indonesian migrant workers in Malaysia; (2) to understand the typology of nationalism among Indonesian migrant workers in Malaysia; and (3) to examine the influences factors behind the nasionalism among Indonesian migrant workers in Malaysia. This is qualitative analysis sumplemented by structured interview as well as focus group discussion (FGD). The systematic content analysis on some particular documents is also applied in this study.